A The Strategic Role of Teachers and Innovation in Learning Media in Early Childhood Education - Gunawan, Hadi; Laura, Angel (Kiddie: Early Childhood Education and Care Journal, 2025)
Early childhood education is a critical phase in development that requires special attention from educators, especially teachers. In this context, the role of teachers is very important in creating effective and meaningful learning experiences, where teacher ethics and learning media innovation are inseparable aspects. This article identifies challenges in early childhood education, including the lack of innovation in learning media and the importance of ethics in interactions between teachers and students. The research method used is literature study, by collecting and analyzing various relevant literature sources regarding the role of teachers, teaching ethics, and the use of learning media. The results of the discussion show that teacher ethics functions as a moral foundation that influences the quality of interactions in education, while learning media innovation is proven to increase children's involvement and motivation. This article concludes that a combination of strong ethics and a creative learning media approach is the key to achieving quality education for early childhood.